Expressed emotion and treatment outcome in higher levels of care for eating disorders. Issue 3 (30th December 2022) - Rienecke, Renee D.; Gorrell, Sasha; Johnson, Madelyn; Duffy, Alan; Mehler, Philip S.; Le Grange, Daniel
Abstract: Objective: Expressed emotion (EE) among caregivers toward the affected offspring is a negative prognostic indicator for adolescent patients with eating disorders (EDs) in outpatient treatment. Less research has examined its impact on adolescents in higher levels of care (HLOC). The current study examined differences in caregiver EE according to the subtype of anorexia nervosa (AN) (restricting [AN‐R] versus binge/purge [AN‐BP]), and level of care (LOC). We also examined the main effects of baseline caregiver EE (emotional overinvolvement [EOI] or criticism), AN subtype, and their interaction on eating pathology and depression at discharge. Method: Adolescent patients ( N = 203) receiving treatment at HLOCs completed measures of ED pathology (Eating Disorder Examination‐Questionnaire) and depression (Patient Health Questionnaire‐9) at baseline and discharge, and one caregiver of each patient completed a measure of EE (Family Questionnaire) at baseline. Results: No differences in caregiver EE were found between patients with AN‐R versus AN‐BP, or relative to LOC. Caregiver EE did not predict outcome for ED symptoms or depression at discharge. Discussion: The impact of high caregiver EE may be less substantial at HLOCs than outpatient care given that caregivers are less involved in treatment at HLOCs. Future research is needed to determine if high caregiver EOI leads to poor treatment outcome for adolescents as it does for adults, or whether it is an appropriate expression of care for patients who are ill enough to require HLOC treatment. Public significance statement: High caregiver EE was not found to predict treatment outcome for adolescents with eating disorders in higher levels of care (HLOCs), possibly due to the limited involvement of caregivers in HLOCs. However, patients step down to outpatient treatment, where high caregiver EE can have a significant negative impact on outcome. HLOCs should incorporate efforts to reduce high caregiver EE in anticipation of step‐down to outpatient treatment.